PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING (SFAE) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA 5 SMAN 9 PEKANBARU TAHUN AJARAN 2013/2014 - Fraditia Wiranti; Yustina Yustina; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTClass Action Research has been conducted that aimed to increase activity and learning result of biology through implementation of Cooperative Model Type SFAE in student of class XI IPA 5 at SMAN 9 Pekanbaru. This researsch conducted on October – November 2013 with research subject were student of class XII IPA 5 at SMAN 9 Pekanbaru consist of 36 student ( 13 boy students and 23 girl students). The parameter of this research were student activity (indicator : tutorial explaining concept, doing discussion, cooperative, asking question and group presentation), teacgher activity (indicator : preface activity, core activity and closing activity), and learning result (indicator : reserve capacity and student thoroughness). The result showed that mean of student activity in cycle I were 66,98% (less category) and cycle II were 80,64% (enough category) , increased 13,75%. Mean of teacher activity in cycle I were 95,5% (very kind category) and cycle II were 100% (very kind category), increased 4,55%. Mean of reserve capacity has increase with cycle I were 81,1% (enough category) and cycle II 84,3% (kind category). Student thoroughness has increased with cycle I were 80,5% (enough category) and cycle II 88,8% (kind category). Thus, the implementation of Cooperative Model Type SFAE could increase activity and learning result of biology in student of class XI IPA 5 at SMAN 9 Pekanbaru study year 2013/2014.Keywords : Cooperative Model Type Student Facilitator And Explaining (SFAE), learning activity, leraning result.